Pengaruh Jumlah Penduduk dan Upah Minimum Regional Terhadap Kriminalitas di Kota Palangkaraya - Rima Harati (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of population size and regional minimum wage on crime in Palangkaraya City. The research location is Palangkaraya City, covering the period 2016-2025. The analytical tools used were multiple regression analysis and classical assumption testing using SPSS 22. The analysis concluded that population size and regional minimum wage do not significantly influence crime in Palangkaraya City. The classical assumption testing concluded that the regression model met the normality test, that there was no multicollinearity in the regression model used, that there were no symptoms of heteroscedasticity in the regression model used, and that there were no symptoms or problems of autocorrelation in this regression model